Analisis Kewenangan Penyidikan Dalam Pelanggaran Wilayah Udara Indonesia (Tinjauan Peran Penyidik PNS dari Kementerian Perhubungan dan TNI AU) - Lusia Sulastri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
This study aims to examine the investigation and the role of civil servant investigators from the Ministry of Transportation and the Indonesian Air Force in conducting normative investigations of violations of Indonesian airspace. The results of the study show that investigations into violations of Indonesian territory cannot be interpreted as the attributive authority of PPNS of the Ministry of Transportation. Based on the grammatical and authentic Article 399 of Law no. 1 of 2009 concerning Aviation clearly does not rule out the possibility of the Indonesian Air Force being an investigator, it's just that whether the Indonesian Air Force already has PPNS, the main indicator of the operation of law enforcement in airspace violations. Article 10 of Law Number 34 of 2004 concerning the TNI and Article 399 of Law No. 1 of 2009 concerning Aviation, the Indonesian Air Force allows inspection of airspace violations, as long as they have PPNS. The role of the Indonesian Air Force in tackling violations of Indonesian airspace as investigators carries out active air defense operations, including detection, and prosecution in the form of shadowing, dispelling (intervention), forced landing (force down) and preparation (destruction). The role of PPNS from the Ministry of Transportation is as an investigator in violations of Indonesian Airspace. However, all cases never reach the judicial process, only issuing diplomatic complaints to the violator's country of origin.